Decision Support System for Providing Social Assistance for Poverty in Manyaran Village Semarang With AHP And Smart Methods - Fauzhan, Yoga Agus; Supriyanto, Aji (Universitas Teknokrat Indonesia, 2025)
One of the problems still faced by the Indonesian state is the problem of poverty. The problem of poverty is a complex problem, especially those who often experience problems in the distribution of poverty social assistance is Manyaran village where the distribution of poverty social assistance is still not optimal. Using the Analytical Hierarchy Process (AHP) and Simple Multi Attribute Rating Technique (SMART) methods used for ranking social assistance in Manyaran Semarang village. The AHP method is used to weight poverty criteria according to the Central Bureau of Statistics (BPS), while the SMART method is used to rank 45 alternatives in Manyaran Semarang. The resul ts of the above ranking obtained the ranking order of alternatives, the first rank got a value of 0.9209 obtained by (A37), while the last rank got a value of 0.0732 obtained by (A15).